Teachers’ Pedagogical Content Knowledge in Technical Schools: The Case of Domestic Installation and Wiring Teaching - Mqondiso Blayi; Ndlelehle Skosana; Samuel Khoza (Research in Social Sciences and Technology, 2022)
Domestic installation and wiring are still a concern among the secondary central district schools of Johannesburg. Students reach the to Grades 11 and 12 with signs of inadequate knowledge on the domestic installation and wiring concepts taught in 10. This is a qualitative research study involving six electrical technology teachers from schools within the central district of Johannesburg, South Africa. The teachers were purposively selected to take part in the study. The pedagogical content knowledge construct was used as a theoretical framework to underpin the study. Data were collected using face-to-face interviews with the teachers and by observing the classroom when teachers were teaching domestic installation and wiring concepts. Data were analyzed using verbatim quotes for face-to-face interviews and descriptively for classroom observations. Findings of the study revealed that teachers are being negatively affected by lack of resources and of adequate training. The study recommends that more resources be sought so that teachers can fully teach the practical component with ease and confidence. Recurrent refresher training events are also recommended for teachers to keep up with the electrical technology concept.